Digitization of Microfinancing Operational Procedures - Andres, Judith L.; Narsico, Lalaine O.; Narsico, Peter G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study delves into the crucial theme of enhancing income-generating capacity, recognizing its pivotal role in meeting basic human needs and catalyzing prosperity within communities. The motivation behind this research lies in addressing this significant issue through the lens of microfinancing, a viable solution to the identified problem. Focusing on a group of microfinancing units strategically located in North Cotabato, Philippines, this study follows the experiences of personnel within these units. The integration of digitization into their operational procedures aimed to elevate service efficiency, providing a contemporary solution to the challenges faced. The research methodology employed was qualitative, utilizing purposive sampling to gain in-depth insights. Observations, interviews, and informal conversations with key informants, including loan officers, branch managers, and an area monitor, were integral to the inquiry. Both physical and electronic documents played a crucial role in enriching the data collected. Specifically, the study aimed to identify both digitized and non-digitized operational procedures, elucidate the experiences of microfinancing employees concerning these procedures, observe the effects of digitization, and pinpoint immediate improvements resulting from digitization. Key conclusions emerged from the study. Notably, loan processing was identified as the sole procedure yet to undergo digitization. The digitized procedures, encompassing data management, loan disbursement, repayment tracking, and financial reporting, demonstrated notable advantages, characterized by increased speed and reduced errors. Importantly, personnel satisfaction with digitized operational procedures witnessed a positive upturn. Identified improvements that underscore these findings include digitizing loan processing, optimization of loan officers' client-handling capacity, and fortifying institutional data security.